Real-time metabolic monitoring under exhaustive exercise and evaluation of ventilatory threshold by breathomics: Independent validation of evidence and advances - Pugliese, Giovanni; Trefz, Phillip; Weippert, Matthias; Pollex, Johannes; Bruhn, Sven; Schubert, Jochen K.; Miekisch, Wolfram; Sukul, Pritam (Frontiers in Physiology, 2022)
Continuous analysis of exhaled volatile metabolites surrogated in vivo physio-metabolic status under exercise. Prospective validation of precedent proofs within an advanced independent setup may propel breathomics into sports science. Non-invasive optimizations of exercise and diet for athletes or amateurs and of routine therapeutic/rehabilitation training will be of potential interests. Here, an ergometric ramp exercise protocol was performed by healthy adults until exhaustion. Real-time mass-spectrometry based continuous analysis of exhaled metabolites along with breath-resolved spirometry and heart rate monitoring were executed. Arterial blood lactate level was analyzed at defined time points. Exhalation of many blood-borne volatiles changed significantly with the course of exercise and increasing workloads. Such changes mirrored ventilatory and/or hemodynamic effects and diversely depended on the origin and/or physicochemical properties of the substances. Profiles of potentially endogenous hemiterpene, organosulfur, aldehydes, short-chain fatty acids (SCFAs) and ketone etc. showed potential physio-metabolic milieu between muscular vasoconstriction, compartmental distribution of perfusion, extra-alveolar gas-exchange and energy homeostasis etc. Observed trends in exogenous aromatic and nitrile remained related to endogenous isoprene due to their similar solubility and volatility. As evidenced earlier by Schubert, assignments of anaerobic threshold were possible via breath acetone within the present setup. Breathomics enabled instant profiling of physio-metabolic effects, lactate and ventilatory thresholds during exercise. We have successfully validated our previous observations and method within this independent cohort for the first time. Organosulfur and SCFAs turned out to be interesting for investigations of combined diet and exercise programs. Reproducible metabolic breath patterns have enhanced scopes of breathomics in sports science/medicine.